CSA Platform Annual Meeting - November 2019 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
“We are here to make a breakthrough in climate-smart agriculture (CSA) technologies,” announced Ato Dejene Abesha, Secretariat Coordinator for the Rural Economic Development and Food Security (RED&FS) Sector Working Group at the Ministry of Agriculture (MoA), at the kick-off of the CSA Platform Meeting. In his opening remarks, he presented the five guiding principles of the country’s CSA Task Force (CSA-TF), set to implement CSA at the ground level across rural Ethiopia: i) government ownership and leadership; ii) alignment; iii) harmonization and coordination; iv) managing for results; v) mutual accountability. The objectives of the CSA-TF are to share information and create knowledge on CSA as well as build integrative approaches to harness food security, sustainable development and climate action. The workshop centered around reviewing the CSA-TF’s progress, sharing experiences of international organizations and debating in plenary discussions.